Yb3+ doping effects on thermal conductivity and thermal expansion of Yttrium aluminium garnet - Wang, Jing; Xu, Fang; Wheatley, R.J.; Neate, Nigel C.; Hou, Xianghui (Elsevier, 2016)
Yttrium Aluminium Garnet (YAG) is an attractive candidate as thermal barrier material used for turbine blade in aero engines, due to its relatively low thermal conductivity, low oxygen diffusivity and good phase stability at high temperature. YAG has a complex crystal structure, in which Y3+ ions locate in dodecahedron and Al3+ ions in octahedron and tetrahedron. Replacing the host cations with rare earth elements can cause the structure change which influences the thermal properties of YAG. Because the space inside the octahedron is relatively small, Yb3+ ions which have the smallest ionic radial size in the lanthanide series, have been selected and attempted to be doped on dodecahedral and octahedral sites to investigate the effects on thermal conductivity and thermal expansion. The variation of lattice constant indicates that Yb3+ ions are located on the dodecahedron or octahedron. In addition, when Yb3+ ions replace Al3+ ions on octahedral sites, the thermal conductivity at room temperature is dramatically reduced and the coefficient of thermal expansion is over 10×10−6 K−1 at high temperature, which results from the expansion of octahedron due to the much larger radius of Yb3+ ion compared with the host cation (Al3+ ion). On the contrary, replacing Y3+ ions with Yb3+ ions in dodecahedron, the thermal conductivity also gradually reduces to the similar value but the coefficient of thermal expansion is getting smaller, due to the relatively small ionic radius of Yb3+ causing the contraction of the dodecahedron. Therefore, a dopant with much larger radius would be preferred in both dodecahedron and octahedron to significant reduce thermal conductivity as well as increase coefficient of thermal expansion of YAG, by introducing large radial difference between the dopant and the host cations.